Serum cholecystokinin, basal acid secretion, and infantile pyloric stenosis. Issue 10 (October 1979) - Rogers, I M; Drainer, I K; Dougal, A J; Black, J; Logan, R
Abstract : The fasting serum cholecystokinin-like activity was measured in 21 infants with pyloric stenosis and in 13 normal controls. No significant difference was found between the two groups. The basal acid secretion was measured by continuously aspirating the previously emptied stomach for one hour. The basal gastric volume and the total and the free acidity were all greater in the pyloric group.